Evaluation of CD19+CD5+B (B1) Lymphocytes and CD20+CD38 Low Preplasmablast Cells in Patients with Behcet's Disease - Kandi, Basak; Ilhan, Fulya; Cicek, Demet; Demir, Nesrin; Bulut, Vedat; Ucak, Haydar; Halisdemir, Nurhan (Ortadogu Ad Pres & Publ Co, 2011)
Objective: Behcet's disease (BD) is a chronic, recurrent, inflammatory disease. CD19+CD5+ B cells are currently defined as B1 cells and they produce polyreactive antibodies. CD2O+CD38 low B cells can cause endothelial cell adhesion and are responsible for specific antibody synthesis. The aim of this study was to investigate the presence of CD19+CD5+ B cells and B cells containing CD2O+CD38 low molecule, which plays a role in B cell differentiation and activation. Moreover, the ratio of these cells in BD patients was also evaluated. Material and Methods: In this study, 20 BD patients and 20 healthy control subjects were compared. Blood samples of the patients and the control group were stained with standard procedure using CD3, CD19, CD20, CD5, CD38 monoclonal antibodies with flow cytometric method, and B lymphocyte subgroups were evaluated. Results: There were no significant differences between total T and B lymphocyte ratios of two groups. However, CD19+CD5+ B lymphocytes and CD2O+CD38 low preplasmablasts were significantly higher in BD patients compared to the control group. Conclusion: It was determinated that high levels of CD2O+CD38low and CD19+CD5+ B lymphocytes in BD concerns the possible role of humoral immunity or force of T cell independent response. On the other hand, immediate differentiation of IgM producing cells indicates B cell activation and all the others support the possible role of CD38 in the etiology of vasculitis, which is the unchangeable characteristic and the basis of defining BD as an autoinflammatory disease.
Behçet hastalannda CD19+CD5+ B (Bl) lenfositler ile CD20+ CD38 düşük preplazmablast hücrelerinin de?erlendirilmesi
Keywords: Behcet syndrome; B-lymphocytes; lymphocytes